(untitled) (Biocenosis, 2021)
Abstract: Geodiversity represents great value. It is Earth’s memory, the support of ecosystems, and an economic, scientific, and didactic resource. It establishes a link with local culture by connecting and rating the territory. For this reason, conservation measures need to be implemented. Unfortunately, lack of awareness and economic pressures end up affecting geodiversity. For this reason, it is necessary to develop environmental education strategies that enable geo-conservation. The article presents the problem of geodiversity in Tandil, Argentina, and the need to give a more predominant role to environmental education in order to consolidate a long-term conservation process.